2013
DOI: 10.1063/1.4794845
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of laser to x-ray conversion with a low density gold target

Abstract: X-ray emission from laser-plasma interaction is an important x-ray source, and improving laser to x-ray conversion is imperative for various applications. The laser to x-ray conversion efficiency (CE) was simulated for gold targets with different initial densities. Using a 0.1 g/cm3 Au layer target, an x-ray conversion efficiency of 50.8% was obtained, which was 1.34 times of the 37.9% for the solid density target. It has been shown that the enhancement of the x-ray conversion efficiency is caused by the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…[33][34][35] Accordingly, we proposed to increase the conversion efficiency of laser to X rays by using lowdensity gold foam targets based on the simulation of radiation hydrodynamics. 29,30 It was found that for the low-density foam gold target, the radiation ablation process is in the stage of supersonic heat wave and the shock wave behind the supersonic heat wave causes larger x-ray radiation emission and smaller kinetic energy loss. 36 Corresponding experiments which will be summarized in another paper have been performed to confirm its feasibility.…”
Section: Simulations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] Accordingly, we proposed to increase the conversion efficiency of laser to X rays by using lowdensity gold foam targets based on the simulation of radiation hydrodynamics. 29,30 It was found that for the low-density foam gold target, the radiation ablation process is in the stage of supersonic heat wave and the shock wave behind the supersonic heat wave causes larger x-ray radiation emission and smaller kinetic energy loss. 36 Corresponding experiments which will be summarized in another paper have been performed to confirm its feasibility.…”
Section: Simulations and Discussionmentioning
confidence: 99%
“…In practice, the absorbed laser energy of high-Z planar target with free boundaries is mainly transferred to three portions: kinetic energy, internal energy, and radiation energy. [28][29][30] In order to have higher x-ray emissions, the energy balance of the Au-Gd mixture is supposed to be different with that of the pure Au target. Based on our simulation, the internal and kinetic energy fraction for the Au target are 22.5%, and 34.3%, respectively.…”
Section: Simulations and Discussionmentioning
confidence: 99%
“…A considerable amount of work has been done already for X-ray enhancement using metal doped (Ti and Ge) low density silicon oxide foam targets (Fournier et al, 2004;Fournier et al, 2009). In the previous work (Shang et al, 2013), the X-ray conversion efficiency in the case of gold foam was found to increase by 1.34 times as compared to solid gold in the range of multi-eV to multi-keV due to a larger absorption of laser light via inverse bremmstrahlung.…”
Section: Introductionmentioning
confidence: 88%
“…The use of low density targets has been proven as a prominent condidate for the enhancement of X-ray emission from Laser Produced Plasmas (LPP). Many targets such as gold foam (Shang et al, 2013), hydrocarbon based foam (Chaurasia et al, 2015), carbon foam (Chaurasia et al, 2010), structured surfaces (Krishnamurthy et al, 2015;Rajeev at al., 2003), porous Si (Nishikawa et al, 1997), agar agar foam (Limpouch et al, 2006) are used for this 4 purpose. A considerable amount of work has been done already for X-ray enhancement using metal doped (Ti and Ge) low density silicon oxide foam targets (Fournier et al, 2004;Fournier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Simulations were performed with the widely used one dimensional multi group radiation hydrodynamics code Multi. 27,28 The hydrodynamic equations are solved in a Lagrangian formulation with coupled thermal radiation transport, heat conduction, and laser energy deposition mechanism of inverse bremsstrahlung. The experimental laser pulses are adopted as input laser parameters, and the flux limiter is set as 0.05.…”
Section: Resultsmentioning
confidence: 99%